PENERAPAN METODE SECI BERBASIS KNOWLEDGE SHARING UNTUK WEBSITE E-LEARNING SMK AL-WAHYU JAKARTA - Yamin Nuryamin (LPPM Universitas Bina Sarana Informatika, 2016)
SMK al-wahyu is an organization that move in in the science education, as an organization who has been standing would have many the sciences knowledge need to shared with others in this research writer tries to identify the knowledge asset and knowledge procces that is in smk al-wahyu, then design kms based e-learning that can be applied to smk al-wahyu, so as to be manageable knowledge his servants namely teachers through right methods so that it can be motivate teachers in making writing scientific more creative and innovative with support the process knowledge (seci). Research the this analyze the condition of knowledge asset and knowledge process which is with smk al-wahyu , by taking into account infrastructure support information technology that is. Seci method used as framework used to know tacit and explicit in organization, that is a method of research aimed at know kecendrungan and filiation between leadership, culture and technology .The purpose of this research is to make an application e-learning based knowledge sharing that can be applied to smk al-wahyu so as to create knowledge management system ( kms a good and could support the teaching process in schools. To be able to solve the problems have shown above, So needs a knowledge management system which adjusted with needs, for that digunakanlah analysis seci as a framework labor as approach in the analysis knowledge management system.Research methodology used is descriptive qualitative survey, the interview, and documentation as a method of data collection.Primary data derived from the spread of the questionnaire to 80 respondents consisting of teachers, students and the school principal to get a general and needs application that will Applied.A method of design a system used was the 10-step km road map model tiwana. Result from the study is an application website e-learning based knowledge management system (kms) in which there are features required in the process of knowledge sharing in smk al-wahyu.